“When the wind blows, it hurts” – Neuromylitis Optica presenting with Paresthesias and Allodynia - Hicklin, Justin; Varkey, Thomas; Kloft, Luke (Nepal Journal of Neuroscience, 2023)
Patients with Neuromyelitis Optica Spectrum Disorder (NMOSD) and Multiple Sclerosis (MS) often present with similar, nonspecific symptoms. The relationship between the two diseases has long been disputed and their comparable presentation often creates a challenge in diagnosing patients on presentation alone. In this particular case, we present a patient that has symptoms, imaging, and a physical exam pointing to a likely diagnosis of MS. Further abnormal MRI findings continued high concern for possible early-stage MS. However, cerebrospinal fluid analysis yielded findings that revised the diagnosis to NMOSD. This particular case is intriguing as it demonstrates the importance of completeness of work up as this in the end changed the management of the patient.